IMPACT OF CHILD DOMESTIC LABOUR ON CHILD POVERTY : A CASE STUDY OF LUSAKA CITY IN ZAMBIA - Patrick Chanda (European Scientific Journal, ESJ, 2014)
The challenge posed by child domestic labour remains very large in Zambia. Children forced out of school and into labour to help their families to make ends meet are denied the opportunity to acquire the knowledge and skills needed for gainful future employment, thereby perpetuating the cycle of poverty in the family. Child labour therefore not only violates children's rights, but also has consequences for social development in Zambia. This study therefore sought to investigate the impact of child domestic labour on child poverty in Lusaka City of Zambia. The study employed an exploratory qualitative case study design. Data collection methods included semi-structured interviews and document analysis. Child domestics, parents and social workers were purposively sampled for study. Snowball was also applied to locate children. The results of the study showed that children who engage in domestic work come from households affected by HIV/AIDS, and families whose income and education levels are very low. Child domestic employment perpetuates child poverty, resulting in cycle of poverty among children and their families because it deprives children of schooling opportunities and lifelong skills which they can use to fight poverty. Inadequate government legislation poses a challenge to address child poverty and protect the rights of children against child labour and abuse. In order to address poverty and other vulnerabilities that lead children to engage in domestic work, child-sensitive social protection policies and poverty alleviation programmes should be devised by the Zambian government.